Structural Characterization of Amadori Rearrangement Product of Glucosylated Nα-Acetyl-Lysine by Nuclear Magnetic Resonance Spectroscopy. (17th April 2014) - Li, Chuanjiang; Wang, Hui; Juárez, Manuel; Ruan, Eric Dongliang
Abstract : Maillard reaction is a nonenzymatic reaction between reducing sugars and free amino acid moieties, which is known as one of the most important modifications in food science. It is essential to characterize the structure of Amadori rearrangement products (ARPs) formed in the early stage of Maillard reaction. In the present study, the N α -acetyl-lysine-glucose model had been successfully set up to produce ARP, N α -acetyl-lysine-glucose. After HPLC purification, ARP had been identified by ESI-MS with intense [M+H] + ion at 351  m/z and the purity of ARP was confirmed to be over 90% by the relative intensity of [M+H] + ion. Further structural characterization of the ARP was accomplished by using nuclear magnetic resonance (NMR) spectroscopy, including 1D 1 H NMR and 13 C NMR, the distortionless enhancement by polarization transfer (DEPT-135) and 2D 1 H- 1 H and 13 C- 1 H correlation spectroscopy (COSY) and 2D nuclear overhauser enhancement spectroscopy (NOESY). The complexity of 1D 1 H NMR and 13 C NMR was observed due to the presence of isomers in glucose moiety of ARP. However, DEPT-135 and 2D NMR techniques provided more structural information to assign the 1 H and 13 C resonances of ARP. 2D NOESY had successfully confirmed the glycosylated site between 10-N in N α -acetyl-lysine and 7′-C in glucose.